Community structure of metazoan parasites in Hemibrycon surinamensis (Characidae) from the Matapi River in the State of Amapá, Brazil - SOUSA,BRIANI O. (2019)
Abstract Abstract: The aim of this study was to investigate the community of metazoan parasites in Hemibrycon surinamensis from the Matapi River, State of Amapá, Brazil. Among the 31 examined fish, 77.4 % were parasitized by Jainus hexops, Tereancistrum ornatus (Monogenea), Contracaecum sp. (Nematoda), Clinostomus marginatum and Posthodiplostomum sp. (Digenea). However, the dominance was of monogeneans J. hexops and T. ornatus, and among the endoparasites, the predominance was of species at the larval stage. The parasites showed random dispersion. Brillouin diversity index varied from 0 to 0.9, evenness from 0 to 0.7 and species richness from 0 to 3 parasites per host. Low levels of parasitic infection were observed and discussed. The results indicate that this intermediate host occupies a low position in the food web. This is the third eco-epidemiological study for H. surinamensis.